An empirical analysis of the state of competition in OECD mobile wireless markets - Nakil Sung; Mi-ae Kwon (International Telecommunications Society (ITS), 2011)
Contra the current trend of deregulation, mobile wireless markets in the OECD member states appear, until recently, to have been more or less concentrated. The study estimates the equations for market concentration, mobile prices, and profits using annual panel data from 24 OECD member states for the 1998-2009 period, in order to assess their interaction. Mobile prices, measured by revenue per minute in constant USD PPP, are regarded as a direct measure of consumer welfare. Estimation results indicate that in the second half of the 2000s, market concentration had no effect on mobile prices, whereas the positive relationship between market concentration and profits persisted. In other words, the market-power hypothesis is rejected in the second half of the 2000s. This empirical result provides a strong case for a recent lenient approach towards regulation and merger attempts in OECD mobile wireless markets. Additionally, the study provides evidence that regulatory policies have affected mobile market structure and performance.
Keywords: L11; L96; 330; Mobile wireless markets; market structure; market performance; regulatory policy; competition